2022
DOI: 10.25259/sni_598_2022
|View full text |Cite
|
Sign up to set email alerts
|

Clear-cell renal cell carcinoma and glioblastoma multiforme coexistence: Double primary malignancy, does it have a causal relationship?

Abstract: Background: Multiple primary malignancies (MPMs), especially coexistence of renal cell carcinoma (RCC) and glioblastoma multiforme (GBM), are rare. The most likely clinical diagnosis in patient with tumor in another organ is metastatic brain tumor. Although GBM is the most common brain tumor, it is rarely coexistent with other malignancies. Case Description: A 64-year-old female presented with headache and dizziness, along with abdominal pain for 2 weeks before being admitted. The abdominal computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Simanjuntak et al have admirably described both their case and Franke et al's cases; we refer readers to review Simanjuntak et al for a complete description of these cases. [2,10] We have subsequently identified two case reports not described by Simanjuntak et al, a recently reported case series/database analysis including 126 cases of RCC followed by GBM, and an investigation of malignancies in long-term survivors (LTS) of GBM that describes one RCC arising in a patient with an existing GBM diagnosis. [4,8,9,11] A brief overview of all cases is found in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Simanjuntak et al have admirably described both their case and Franke et al's cases; we refer readers to review Simanjuntak et al for a complete description of these cases. [2,10] We have subsequently identified two case reports not described by Simanjuntak et al, a recently reported case series/database analysis including 126 cases of RCC followed by GBM, and an investigation of malignancies in long-term survivors (LTS) of GBM that describes one RCC arising in a patient with an existing GBM diagnosis. [4,8,9,11] A brief overview of all cases is found in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Death from GBM Long-term survivor of GBM who later developed RCC Simanjuntak et al [10] 2022 64, F Concurrent Right temporal lobe…”
Section: Craniotomy and Brain Radiotherapy Nephrectomymentioning
confidence: 99%
See 3 more Smart Citations